(untitled) (World Bulletin of Social Sciences, 2024)
In this article, one of the modern and actual problems is the concept of tolerance, its formation, religious and educational tolerance, high thinking, principles of spiritual, cultural, ideological, humanitarian tolerance, the formation of humanitarian qualities in children of primary and preschool age and ways of education are discussed.